PENGARUH PENGEMBANGAN ORGANISASI DAN MODAL SOSIAL TERHADAP KINERJA DENGAN DIMODERASI RESISTANCE TO CHANGE : (Studi Pada Pegawai KPP Pratama Demak) - Yusup; Euis Soliha (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
The aim of the research is to analyze and describe the influence of organizational development and social capital on the performance of KPP Pratama Demak employees. To analyze and describe resistance to change moderating the influence of organizational development and social capital on the performance of KPP Pratama Demak employees. The population in this study were KPP Pratama Demak employees. The sample for this research was all KPP Pratama Demak employees, totaling 75 employees. Sampling was taken using census sampling technique. The data collection method uses a questionnaire. Data analysis uses linear regression analysis. Based on the research results, it can be concluded that organizational development has a positive effect on the performance of KPP Pratama Demak employees. Social capital has a positive effect on the performance of KPP Pratama Demak employees. Resistance to change was unable to moderate the influence of organizational development on the performance of KPP Pratama Demak employees. Resistance to change was unable to moderate the influence of social capital on the performance of KPP Pratama Demak employees.